Adenosine Monophosphate-Activated Protein Kinase Signaling Regulates Lipid Metabolism in Response to Salinity Stress in the Red-Eared Slider Turtle Trachemys scripta elegans - Hong, Meiling; Li, Na; Li, Jiangyue; Li, Weihao; Liang, Lingyue; Li, Qian; Wang, Runqi; Shi, Haitao; Storey, Kenneth B.; Ding, Li (Frontiers in Physiology, 2019)
Aquatic animals have developed various mechanisms to live in either hyperionic or hypoionic environments and, as such, not many species are capable of surviving in both. The red-eared slider turtle, Trachemys scripta elegans, a well-known freshwater species, has recently been found to invade and inhabit brackish water. Herein, we focus on some of the metabolic adaptations that are required to survive and cope with salinity stress. The regulation of the AMP-activated protein kinase (AMPK), a main cellular “energy sensor” and its influence on lipid metabolism were evaluated with a comparison of three groups of turtles: controls in freshwater, and turtles held in water of either 5‰ salinity (S5) or and 15‰ salinity (S15) with sampling at 6 h, 24 h, 48 h and 30 d of exposure. When subjected to elevated salinities of 5‰ or 15‰, AMPK mRNA levels and AMPK enzyme activity increased strongly. Salinity-activated AMPK promoted the expression of the peroxisome proliferator activated receptor-α (PPARα) transcription factor that, in turn, facilitated upregulation of target genes including carnitine palmitoyltransferase (CPT) and acyl-CoA oxidase (ACO). Elevated AMPK also led to inhibition of transcription factors involved in lipid synthesis, such as the carbohydrate-responsive element-binding protein (ChREBP) and sterol regulatory element binding protein 1c (SREBP-1c), as well as significantly decreasing two of their target genes, acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS). Exposure to saline environments also increased plasma triglyceride (TG) content. Interestingly, the content of low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) in serum were markedly higher than control levels in the S15 group after 30 days, which indicated that lipid metabolism was disrupted by chronic exposure to high salinity. These findings demonstrate that activation of AMPK regulates lipid metabolism in response to salinity stress through the inhibition of lipid synthesis and promotion of lipid oxidation in the liver of T. s. elegans. This may be an important component of the observed salinity tolerance of these turtles that allow for invasion of brackish waters.